Production of Starch-Based Bioplastic from Durio zibethinus Murr Seed Using Glycerol as Plasticizer - Jannah, Nanda Raudhatil; Jamarun, Novesar; Putri, Yulia Eka (Universitas Andalas, 2021)
Bioplastics are bio-based plastics from natural resources, made to replace conventional plastics. The utilization of biopolymers in bioplastics provide a faster degradation compared to petroleum-based plastics. Starch-based bioplastic from mixing Durio zibethinus Murr starch and glycerol as plasticizer have been conducted. In this research, the concentration of glycerol has been varied to study the effect on starch-based bioplastics mechanical properties. The tensile strength for Durio zibethinus Murr starch-based bioplastic with 20% glycerol was 50.28 MPa with 13.3% elongation. The functional group found on the Fourier transform infrared spectroscopy (FTIR) spectra indicated the presence of O-H stretch, C-H stretch, C=O stretch, and C-O stretch which stated the formation of bioplastic. The image results gained from scanning electron microscope (SEM) showed that the morphology surface of bioplastic was less homogenous and rough. The soil burial test for biodegradability showed Durio zibethinus Murr starch-based bioplastic achieved 38.9% weight loss in a 5-day observation.